2011
DOI: 10.1002/bit.23228
|View full text |Cite
|
Sign up to set email alerts
|

Secreted production of collagen‐inspired gel‐forming polymers with high thermal stability in Pichia pastoris

Abstract: Previously, we have shown that gel-forming triblock proteins, consisting of random coil middle blocks and trimer-forming (Pro-Gly-Pro)(9) end blocks, are efficiently produced and secreted by the yeast Pichia pastoris. These end blocks had a melting temperature (T(m)) of ∼41°C (at 1.1 mM of protein). The present work reveals that an increase of T(m) to ∼74°C, obtained by extension of the end blocks to (Pro-Gly-Pro)(16), resulted in a five times lower yield and partial endoproteolytic degradation of the protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 116 publications
1
29
0
Order By: Relevance
“…Synthetic collagen-based block copolymers are artificially designed constructs and combine some of the approaches mentioned so far. When short collagen-like (GPP) n -peptides are positioned around a hydrophilic unstructured core domain and expressed in P. pastoris, a stable gelatin-like hydrogel can be produced with high yields [77,78]. Since these structures, like engineered collagens, are based on synthetic genes, the addition of short peptide sequences such as cell adhesion motifs or calcification sites is trivial.…”
Section: Collagen-analogues As Basis For Future Biomaterialsmentioning
confidence: 99%
“…Synthetic collagen-based block copolymers are artificially designed constructs and combine some of the approaches mentioned so far. When short collagen-like (GPP) n -peptides are positioned around a hydrophilic unstructured core domain and expressed in P. pastoris, a stable gelatin-like hydrogel can be produced with high yields [77,78]. Since these structures, like engineered collagens, are based on synthetic genes, the addition of short peptide sequences such as cell adhesion motifs or calcification sites is trivial.…”
Section: Collagen-analogues As Basis For Future Biomaterialsmentioning
confidence: 99%
“…PTH (1-84) was also susceptible to yapsins when expressed in S. cerevisiae and the use of multiple-yapsin-deficient mutant was efficient in preventing the proteolytic degradation [5]. YPS1 gene of P. pastoris was first cloned and characterised by Werten and Wolf [24], and the authors found that the yps1 -disrupted P. pastoris strain was beneficial for secreting production of collagen-inspired gel-forming polymers [20]. Besides, Yao et al [26] found that the significant reduction of HSA-AK15 (R13 K) degradation, which occurred in the sequence of AK15 (R13 K), was achieved by the YPS1 disruption in P. pastoris strain.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their high proline content, the end blocks are sufficiently stable to form triple helices in the absence of prolyl-4-hydroxylation (Section 9.1.2). The melting point of (Pro-Gly-Pro)n peptides can be controlled by their length n. Thus, besides T9 end blocks, we also constructed Tn end blocks with n = 6, 12, and 16 [114,115]. The proteins with n = 6 or 9 were produced at several g/L of cell-free broth, and the proteins with n = 12 or 16 at 0.6 and 0.4 g/L, respectively.…”
Section: Collagen-inspired Thermoresponsive Block Copolymersmentioning
confidence: 99%
“…polymers, potentially capable of forming triple helices close to the Glu-Ala repeats, do show low levels of extended species (Chapter 6) [114]. Overexpression of DPAPase A in S. cerevisiae led to increased maturation of α-factor pheromone [163], which suggests this may be a viable strategy for improving the processing of the ppαF leader when used to drive secretion of heterologous proteins.…”
Section: Secretory Leader Processing and Efficiencymentioning
confidence: 99%
See 1 more Smart Citation